2010
DOI: 10.1071/an10030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutritional and socio-sexual cues upon reproductive efficiency of goats exposed to the male effect under extensive conditions

Abstract: This study evaluated the effect of nutritional supplementation and socio-sexual cues upon reproductive efficiency of goats exposed to the male effect under rangeland grazing conditions (22°N). Criollo goats (n = 73) were distributed in four experimental groups: (1) continuous males (CM, n = 19) in which males (n = 2) remained together with females from 7 March to 28 July; (2) supplemented males (SM, n = 16) in which males (n = 2) were kept separately and were individually supplemented with 18% crude protein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…The consumption of grasses, herbaceous, and shrub species, without the consumption of concentrates (grains), explains the higher content of FT found in S2. Other studies have found evidence that the seasonal and environmental changes in food availability promote changes in the reproductive annual pattern (Flores‐Najera et al., ; Meza‐Herrera & Tena‐Sempere, ) and in turn in the quality and quantity of goat milk (Paz, Togo, Usandivaras, Castel, & Mena, ). Also, a reduction in the consumption of concentrates (sorghum) by lactating goats and substitution with orange peel, results in higher milk fat (Hernández‐Meléndez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of grasses, herbaceous, and shrub species, without the consumption of concentrates (grains), explains the higher content of FT found in S2. Other studies have found evidence that the seasonal and environmental changes in food availability promote changes in the reproductive annual pattern (Flores‐Najera et al., ; Meza‐Herrera & Tena‐Sempere, ) and in turn in the quality and quantity of goat milk (Paz, Togo, Usandivaras, Castel, & Mena, ). Also, a reduction in the consumption of concentrates (sorghum) by lactating goats and substitution with orange peel, results in higher milk fat (Hernández‐Meléndez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason behind that may be related to body weight, metabolic status, and age. Certainly, both body weight and metabolic status are a crucial signaling cues activating GnRH neurons and promoting the interaction among the hypothalamic-hypophyseal-gonadal components, resulting in the establishment of reproductive function (Flores-Najera et al 2010;Guerra-García et al 2009;Meza-Herrera et al 2010a, b;Urrutia-Morales et al 2009). Kridli et al (2006a) have shown that Awassi ewe lambs reach puberty at around 280 days of age when they reach 36 kg of body weight.…”
Section: Induced Cycle Reproductive Responsesmentioning
confidence: 97%
“…La heredabilidad de la mayoría de las características económicas es muy baja. Los factores ambientales más importantes que afectan el desempeño reproductivo son: (1) el balance de energía y nutrición, (2) el fotoperiodo y la temporada, (3) los factores socio-sexuales, (4) la temperatura, la humedad, y (5) el estrés (Scaramuzzi y Martin, 2008;Urrutia-Morales et al, 2009;Flores-Najera et al, 2010;González-Bulnes et al, 2010;Meza-Herrera et al, 2010;2011). La reducción de energía disponible o la mala condición corporal afecta el estro y la ovulación impidiendo la liberación hipotalámica de la hormona luteinizante (LH) a partir de la glándula pituitaria anterior.…”
Section: Sheep Of Jordanunclassified
“…The heritability of most economic traits is quite low. The major environmental factors affecting reproductive performance include: (1) nutrition and energy balance, (2) photoperiod and seasonality, (3) socio-sexual factors, (4) temperature and humidity, and (5) stress (Scaramuzzi and Martin, 2008;Urrutia-Morales et al, 2009;Flores-Najera et al, 2010;González-Bulnes et al, 2010;2011). Reduced available energy or poor body condition negatively affect estrus and ovulation inhibiting the hypothalamic release of luteinizing hormone (LH) from the anterior pituitary gland.…”
Section: Introductionmentioning
confidence: 99%